1841 Del. Laws 198, A Supplement to the Act Entitled “An Act for Establishing the Boundaries of the Town of Dover, and for Other Purposes Therein Mentioned, § 2 - (:unkn) unknown (General Publisher, 1841)
Placed a duty on commissioners, justices, and constables to suppress, extinguish, and prevent bonfires in the public square of Dover. Also required the suppression and preventing of discharge of guns, firecrackers, squibs within the town limits.
--
Keywords: DISCHARGE